PROBLEM DOPUSZCZANIA PRZEZ SĄD DOWODÓW Z URZĘDU W POSTĘPOWANIU CYWILNYM - Knoppek, Krzysztof (Wydział Prawa i Administracji UAM, 2007)
The paper is focused on the still controversial issue of the courts of the first and second instance admitting or deciding not to admit ex officio evidence. This issue has become even more problematic after the amendments o f the code o f civil proceedings commenced in 1996. The judicial decisions of the last years have demonstrated an opinion that it is in the courts discretion to decide whether ex-officio evidence should be admitted, and such a decision should be made such evidence has been deemed necessary in a given case. In my opinion this position is wrong and contrary to the current legal order. The admissibility of ex officio evidence by the court should be indeed exceptional and reserved to those very rare situations in which the legally protected goods play a role, or where the courts’ decision is prompted by a relevant special regulation. Generally, however, admitting ex officio evidence may infringe the principle of the equal treatment of the parties, and the principle o f independence and impartiality of the courts adjudicating in civil matters.
ADMISSIBILITY OF EX OFFICIO EVIDENCE BY THE COURTS IN CIVIL PROCEEDINGS